Just Housing: The Moral Foundations of American Housing Policy - Dawkins, Casey J. (London, England : The MIT Press, 2021)
"Just Housing is an interdisciplinary investigation of the idea of "housing justice" in the United States".
Keywords: Housing policy -- United States; Housing -- Moral and ethical aspects -- United States